An Analysis of the Factors Influencing Research Capacity Developments in Higher Education Institutions in Tanzania - Kazoka, James Ernest; Wema, Evans F (University of Dar es Salaam Library Journal, 2021)
The study examined factors influencing efforts towards developing research capacity in Higher Education Institutions (HEIs) in Tanzania. A mixed research approach (quantitative and qualitative) was employed in the study. Accordingly, a cross-sectional survey using questionnaires and semi-structured interview was used to collect primary data from simple randomly and purposively selected academic staff. The study findings show that competences, knowledge, and experiences in conducting research are the attributes that faculty members acquire through short training aimed to enhance competences in conducting research. Factors promoting research capacity development include presence of research policy and awareness of it, motivation to conduct research, availability and adequacy of research funds. Challenges faced were insufficient research skills, poor collaboration between senior and junior academic staff, and lack of pro-activeness and commitment in conducting research. The study recommends that HEIs should regularly organize training on research skills for academic staff and faculty members to be proactive and committed in carrying out research.